Learning from errors in dual vocational education: video-enhanced instructional strategies. Issue 5 (10th July 2017) - Cattaneo, Alberto A.P.; Boldrini, Elena
Abstract : Purpose: Starting from the identification of some theoretically driven instructional principles, this paper presents a set of empirical cases based on strategies to learn from errors. The purpose of this paper is to provide first evidence about the feasibility and the effectiveness for learning of video-enhanced error-based strategies in vocational education and training. Design/methodology/approach: Four different cases are presented. All of them share the same design-based research perspective, in which teachers and researchers co-designed an (iterative) intervention in the field. Two cases are preliminary investigations, while the other two profit from a quasi-experimental design with at least one experimental condition based on error treatment and a control group. Findings: The four cases show the effectiveness of learning from error (and from error analysis). More specifically, they show the validity and flexible adoption of the specific instructional principles derived from the literature review: the use of inductive strategies and in particular, of worked-out examples; the reference to a concrete, possibly personal, experience for the analysis task; the use of prompted writing to elicit self-explanations and reflection; and the use of video for recording and annotating the situation to be analysed. Research limitations/implications: The four cases constitute only a starting point for further research into the use of errors for procedural learning. Moreover, the cases presented are focused on learning in the domain of procedural knowledge and not in that of declarative knowledge. Further studies in the vocational education and training sector might serve this research area. Practical implications: The paper provides concrete indications and directions to implement effective instructional strategies for procedural learning from errors, especially within vocational education. Social implications: Errors are often identified with and attributed to (individual) failures. In both learning institutions and the workplace, this can engender an intolerant and closed climate towards mistakes, preventing real professional development and personal growth. Interventions on learning from errors in schools and workplaces can play a role in changing such a culture and in creating a tolerant and positive attitude towards them. Originality/value: The majority of studies about learning from errors are focused on disciplinary learning in academic contexts. The present set of cases contributed to filling in the gap related to initial vocational education, because they deal with learning from errors in dual vocational training in the field of procedural knowledge development. Moreover, a specific contribution of the presented cases relies on the use of video annotation as a support that specifically enhances error analysis within working procedures.